Diversity-oriented synthesis of nanographenes enabled by dearomative annulative π-extension - Wataru Matsuoka (Nature Portfolio, 2021)
Nanographenes and polycyclic aromatic hydrocarbons (PAHs) are important classes of compounds with numerous applications, but challenging to access due to a lack of programmable and diversity-oriented methods. Here, the authors report a diversity-oriented, growth-from-template synthesis of nanographenes enabled by iterative annulative π-extension reactions from small PAH starting materials.